Inteligencia Española en México : correspondencia Alfonso Reyes-Gustavo Baz (1939-1958) / compilación, presentación y notas de Alberto Enríquez Perea - Baz, Gustavo (1894-) Enríquez Perea, Alberto; Reyes, Alfonso (1889-1959) (Documentos Tavera ; 14)
Índices